Ovarian neoplasia in adolescence: a retrospective chart review of girls with neoplastic ovarian tumors in Saudi Arabia - Lateefa AlDakhil; Asma Aljuhaimi; Mashael AlKhattabi; Saleh Alobaid; Rafif E. Mattar; Abdulaziz Alobaid (BMC, 2022)
Abstract Background Ovarian neoplasia in children and adolescents is a rare tumor. The diagnosis and management of such tumors is often difficult and delayed due to non-specific symptoms and low suspicion. Surgical management that preserves fertility and ovarian function should be the goal. Objective This study aimed to review the clinical presentation, tumor characteristics, and management of Saudi Arabian adolescents. Methods A retrospective chart review was conducted on adolescent girls aged 19 or less admitted to tow referral hospital in Riyadh, Saudi Arabia, diagnosed with adnexal mass over an 8 years' period; patients who were older than 19 were excluded. The data collected from patients' charts included age, presenting symptoms, radiologic findings, type of surgery, specialist who performed the surgery, and histopathology of the tumors. We classified patients according to age using the three WHO developmental stages: early adolescence (10-13 years old), middle adolescence (14-16 years old), and late adolescence (16-17 years old). The statistical study used SPSS version 18.0 to determine the data's frequency, distributions, and means (SPSS Inc., Chicago, IL). Results We analyzed 164 patients, between 10 and 19 years old, admitted to two hospitals between 2009 and 2017. We found that 85% of these patients underwent surgery for adnexal mass removal, and 90.2% were symptomatic or emergency cases. The majority of our patients were post-menarche (96.95%), and were between the ages of 14 and 19. The most common surgical procedure for tumor removal was laparoscopic cystectomy (74.4%). An adnexal mass with a solid component on ultrasound is the most commonly found indicator of malignancy. The majority of tumors were benign (32.3%). Germ cell tumors were the most common (68.7%) malignant tumor, and yolk sac tumors were the most common subgroup of germ cell tumors. When managed by a gynecologist, surgical intervention can be a successful method of preserving fertility. Conclusions Our results confirm that the majority of neoplastic ovarian tumors in children and adolescents are benign, and surgical intervention can be used to maintain fertility, especially when managed by a gynecologist. This is one of the largest reported series and the first from our area.